Predictors of hearing screening among residents of Saudi Arabia at primary healthcare settings in Riyadh: useful insights from a cross-sectional survey - Ibtehaj F. Alshdoukhi; Mamdouh M. Shubair; Ashraf El-Metwally; Rasha Abdullah Alhazzaa; Faris Fatani; Ali Alshehri; Aljohrah Ibrahim Saleh Aldubikhi; Lama Mohammad Alomari; Nouf Binhowaimel; Hanan M. Al Kadri (BMC Public Health)
Abstract Background Despite the significant prevalence of hearing impairment and the devastating impact on the quality of life, screening patterns regarding hearing loss in adults are significantly reduced. It is necessary to identify the proportion of residents of Saudi Arabia which undergo for hearing screening and identify predictors of hearing loss. Therefore, we conducted this study to identify predictors of the hearing screening among residents of Saudi Arabia. Methods A cross-sectional study was undertaken, and an electronic questionnaire was administered to 14,239 patients who visited primary health care centers. Primary health care centers were selected using a random sampling technique. Data was collected on hearing screening and other sociodemographic and behavioural factors along with other co-morbidities. We performed multiple logistic regressions to identify predictors that were significantly associated with hearing screening. We performed analysis using SPSS version 26.0 for Windows and reported adjusted odds ratios (AORs) with 95% CIs. Results The sample consisted of 43.4% males and 65.3% married participants. Only 5.9% of the study participants reported going for hearing screening. Age (AOR: 1.01; 95% CI: 1.01, 1.02); higher education level (AOR: 2.46; 95% CI: 1.55, 3.92), full time employment (AOR: 1.36; 95% CI: 1.05, 1.75), part time employment (AOR: 1.54; 95% CI: 1.22, 1.94), good health status (AOR: 1.52; 95% CI: 1.17, 1.96), and Diabetes Mellitus (AOR: 1.37; 95% CI: 1.08, 1.72) were found to be strong predictors of hearing screening among residents of Saudi Arabia in Riyadh. Conclusion We found a very low prevalence of hearing screening among residents of Saudi Arabia. Older age, educated, employed, people with good status health, and diabetic individuals were more likely to go for hearing screening. Health literacy sessions need to be carried out to raise awareness among residents of Saudi Arabia and more robust epidemiological studies need to be carried out to explore the reasons of low hearing screening in this population.